Is timing of the first antenatal visit associated with adverse birth outcomes? Analysis from a population-based birth cohort. (November 2016) - Alwan, Nisreen A; Roderick, Paul J; Macklon, Nick S
Abstract: Background: Adequate antenatal care can improve maternal and child health outcomes. The UK National Institute for Health and Care Excellence (NICE) recommends that the first antenatal visit with a health-care professional should occur by 10 weeks' gestation. The WHO Focused Antenatal Care Protocol recommends that it happens no later than 16 weeks' gestation. We aimed to examine the associations between timing of the first antenatal booking visit and adverse birth outcomes including low birthweight, preterm birth, and stillbirth. Methods: Antenatal and delivery records from a population-based cohort consisting of all women receiving maternity care at University Hospital Southampton, UK, during 2000–13 were analysed (74 449 pregnancies of which 64 739 had delivery data). We conducted multiple logistic modelling to assess the associations of interest. All models computed a cluster-robust standard error of the difference to account for clustering in women with more than one pregnancy included. Findings: 74 220 pregnancies had booking timing information. Mean gestational age at booking was 12·6 weeks (SD 5·3), with 21 482 pregnancies (29%) having their booking visit by 10 weeks' gestation, 45 015 (61%) by 12 weeks', 59 986 (81%) by 14 weeks', and 65 755 (89%) by 16 weeks'. Of the 64 246 livebirths, 4009 (6·2%) were of low birthweight (<2500 g) and 4253 (6·6%) were preterm (<37 weeks'). There were 302 (0·5%) stillbirths. Pregnancies with a booking visit after 16 weeks' were more likely to lead to low birthweight (odds ratio 1·2, 95% CI 1·04–1·4; p=0·01, adjusted for maternal age, body-mass index, blood pressure, parity, ethnicity, employment status, educational attainment, alcohol consumption, smoking, infertility treatment, baby's sex, and gestational age). Booking after 14 weeks' was associated with preterm birth (1·3, 1·2–1·4; p<0·0001, adjusted for all except gestational age). With the NICE cut-off of 10 weeks', no significant associations were seen with low birthweight (adjusted odds ratio 1·1, 95% CI 1·0–1·2), preterm birth (1·0, 0·9–1·1), or stillbirth (1·1, 0·8–1·5). Interpretation: Delayed first antenatal visit (one in 10 women after 16 weeks' and one in five women after 14 weeks' gestation) was associated with adverse birth outcomes. However, this association could represent residual confounding. A Cochrane review found no effect of reduced versus standard number of antenatal visits on preterm birth and low birthweight, although all included trials recruited women after booking. Emphasis on early booking in primary care is recommended. Funding: None.